THE WAY OF INDEPENDENT DEVELOPMENT IS THE MAIN FACTOR OF INDEPENDENT NATIONAL RECOVERY AND DEVELOPMENT (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Annotation: This article explores the way of independent development is the main factor of independent national recovery and development, how the path of independent development has become the central pillar in Uzbekistan's journey towards prosperity and a brighter future.